2003
DOI: 10.1603/0022-0493-96.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Repellency, and Horizontal Transmission of Fipronil in the Formosan Subterranean Termite (Isoptera: Rhinotermitidae)

Abstract: Toxicity of fipronil was evaluated against field-collected Coptoteres formosanus Shiraki. In topical application assays, fipronil was highly effective against both workers and soldiers at very low doses. Acute toxicity after 24 h was significantly greater in workers than in soldiers. The LD50s were 2.59- and 2.91-fold greater with soldiers than with workers from the two tested colonies. The LD50s of fipronil at 72 h after treatment were <2.0 ng/insect, with no significant differences regarding the tested worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 5 publications
0
30
1
Order By: Relevance
“…Despite that large intercolony differences in response to insecticides is common (Su and La Fage 1984), there were incidences where differences in susceptibility between colonies were not detectable. Osbrink et al (2001) and Ibrahim et al (2003) reported similarity among the Formosan subterranean termite colonies in their susceptibility toward Þpronil.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Despite that large intercolony differences in response to insecticides is common (Su and La Fage 1984), there were incidences where differences in susceptibility between colonies were not detectable. Osbrink et al (2001) and Ibrahim et al (2003) reported similarity among the Formosan subterranean termite colonies in their susceptibility toward Þpronil.…”
Section: Resultsmentioning
confidence: 94%
“…Ibrahim et al (2003) reported an LD 50 Ͻ 2.0 ng per termite after 72-h treatment of the Formosan subterranean termite. They also reported 100% mortality of termites at 48 h after exposure to 50 g sand treated with 10 ml of Þpronil at rates of 0.01Ð 0.125% in a choice assay.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations